2001
DOI: 10.2307/2679798
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Behavioral Responses to Predators Shape the Growth/Predation Risk Trade-Off in Damselflies

Abstract: Most organisms must simultaneously find enough food for themselves while trying not to become food for some other organism. Previous field experiments have shown that larvae of Enallagma and Ischnura species are able to coexist in the littoral zones of lakes because they resolve this growth/predation risk trade-off differently: Ischnura species grow more quickly than Enallagma species, but Ischnura species suffer higher mortality rates than Enallagma. We performed a series of laboratory studies to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
138
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(146 citation statements)
references
References 58 publications
8
138
0
Order By: Relevance
“…UP 1 烯 Ra Our assumption that larger individuals ingest more food than small individuals is supported by a linear increase between body size and food ingested shown in damselflies (McPeek et al 2001). The absolute amount of resources that can potentially be harvested increases linearly with increasing foraging activity and abundance of resources in the environment.…”
Section: Resource Uptakementioning
confidence: 88%
“…UP 1 烯 Ra Our assumption that larger individuals ingest more food than small individuals is supported by a linear increase between body size and food ingested shown in damselflies (McPeek et al 2001). The absolute amount of resources that can potentially be harvested increases linearly with increasing foraging activity and abundance of resources in the environment.…”
Section: Resource Uptakementioning
confidence: 88%
“…energy allocated to other predation-avoidance behaviors) might interact with resource productivity. The presence of a predator has been shown to reduce the growth rate of damselflies through stress effects, without reducing food uptake, which may lower assimilation efficiency and/or increase metabolic rate (Stoks 2001) and differences among 2 damselfly genera in this stress response might facilitate coexistence (McPeek et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated metabolic rate helps keep prey in a heightened state of alertness to increase their escape performance, thereby lowering the likelihood that predators will capture them (Hawlena et al, 2011;Zanette et al, 2011;Clinchy et al, 2013). But elevated metabolism arising from perceived predation risk may change organismal nutrient demand and hence the kinds of resources consumed by prey (McPeek et al, 2001;Hawlena and Schmitz, 2010b;Thaler et al, 2012). This also has implications for organismal fitness, but through a physiological trade-off in nutrient allocation between maintenance, growth, and reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…These shifts in nutrient intake should also be reflected in body element stoichiometry, with stressed prey having higher carbon [C]:nitrogen [N] ratios than non-stressed prey (Hawlena and Schmitz, 2010a). Some experiments have shown that such shifts in nutrient intake and body stoichiometry can indeed occur between conditions with and without perceived predation risk (McPeek et al, 2001;Hawlena and Schmitz, 2010b;Jansens et al, 2015). Other experiments have, however, shown that the predicted responses do not occur (Costello and Michel, 2013;Dalton and Flecker, 2014;Kaplan et al, 2014;Guariento et al, 2015;Kirschman et al, 2016;Van Dievel et al, 2016;Zhang et al, 2016), thereby calling into question the generality of the predicted stress response.…”
Section: Introductionmentioning
confidence: 99%